2016
DOI: 10.1007/s10068-016-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Zygosaccharomyces mellis strains in stored honey and their stress tolerance

Abstract: To screen yeast with high sugar tolerance and evaluate their stress tolerance, six yeast strains were selected from 17 stored honey samples. The species were identified through 26S rRNA sequencing. Their stress tolerance was determined via the Durham fermentation method and ethanol production ability was determined via flask fermentation. The results demonstrated that all the six strains were . Their sugar, ethanol, and acid tolerance ranges were 500-700 g/L, 10-12% (v/v), and pH 2.5-4.5, respectively. The SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
11
0
2
Order By: Relevance
“…A few fungi (yeasts) are well known for their high sugar-concentration and ethanol tolerance and were already described in honey isolates. Some of them are fermentative agents involved in the aroma production of food and beverages [ 40 , 41 , 42 ]; Zygosaccharomyces was the most represented genus in both honeys (about 42% and 60% of reads, respectively), with reads mainly matching a few species ( Z . mellis , Z .…”
Section: Resultsmentioning
confidence: 99%
“…A few fungi (yeasts) are well known for their high sugar-concentration and ethanol tolerance and were already described in honey isolates. Some of them are fermentative agents involved in the aroma production of food and beverages [ 40 , 41 , 42 ]; Zygosaccharomyces was the most represented genus in both honeys (about 42% and 60% of reads, respectively), with reads mainly matching a few species ( Z . mellis , Z .…”
Section: Resultsmentioning
confidence: 99%
“…Physiological characteristics that make the yeast particularly problematic include their ability to ferment sugar, osmotolerance, resistance to preservatives, formation of heat-resistant ascospores and fructophily [21−23]. Recent research by Liu et al [24] confirmed that Z. mellis tolerated sugar, ethanol, and acid at ranges of 500−700 g/l, 10−12% (v/v), and pH 2.5−4.5, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Los géneros Saccharomyces, Schizosaccharomyces, Zygosaccharomyces, Candida y Torulaspora suelen ser descriptos como presentes en la miel (Raspor & Zupan, 2006;Kurtzman & James, 2006;Pitt & Hocking, 2009). Z. mellis, es una especie que puede llegar a fermentar concentraciones de azúcar como las normalmente presentes en la miel, donde otras levaduras se verían inhibidas por efecto de la alta presión osmótica (Liu et al, 2016). T. pullulans, es repetidamente identificada en suelo, hojas y frutos, como una especie dominante (Zhang et al, 2017;Wang et al, 2018).…”
Section: Discussionunclassified
“…Fusarium y Aspergillus también fueron descriptos como frecuentes en muestras de miel (Vica et al, 2009). Si bien, la mayor parte de las levaduras en la miel no pueden crecer o se encuentran como viables pero no cultivables (VPNC), debido principalmente a la alta concentración de azúcar y antimicrobianos (Déak, 2008); se detectó la producción de etanol en algunas muestras de miel almacenada; indicando que hay ciertos tipos de levaduras, que pueden haber sufrido una domesticación natural, y convertir los carbohidratos en etanol, aún bajo alto estrés de azúcar (Liu et al, 2016); y otros tipos de estrés, como, fitoquímicos provenientes del néctar (Herrera et al, 2009;Herrera et al, 2010). En el presente trabajo se buscó aislar distintas especies de levaduras, en lo posible inocuas, y tolerantes a diferentes estrés inherentes a la miel, por su naturaleza antimicrobiana; y que puedan presentar antagonismo hacia mohos patógenos pre-y poscosecha de cultivos.…”
Section: Introductionunclassified